2013
DOI: 10.1890/12-2170.1
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms underlying plant sexual dimorphism in multi‐trophic arthropod communities

Abstract: A growing body of research documents the importance of plant genetic effects on arthropod community structure. However, the mechanisms underlying these effects are often unclear. Additionally, plant genetic effects have largely been quantified in common gardens, thus inflating the estimates of their importance by minimizing levels of natural variation. Using Valeriana edulis, a dioecious plant with genetically based sex determination, we conducted surveys and experiments on wild-grown individuals to document f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
21
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 48 publications
5
21
1
Order By: Relevance
“…Consistent with our results, past studies have shown female plants to recruit more natural enemies (Mooney et al 2012a;Petry et al 2013) by increasing the availability of floral resources that provide nutritional benefits (i.e., nectar) to associated arthropod communities (Ashman and King 2005;Wäckers et al 2005;Pacini and Nepi 2007). Such effects can increase indirect defenses from predators and parasitoids attracted to these floral resources (Cepeda-Cornejo and Dirzo 2010).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Consistent with our results, past studies have shown female plants to recruit more natural enemies (Mooney et al 2012a;Petry et al 2013) by increasing the availability of floral resources that provide nutritional benefits (i.e., nectar) to associated arthropod communities (Ashman and King 2005;Wäckers et al 2005;Pacini and Nepi 2007). Such effects can increase indirect defenses from predators and parasitoids attracted to these floral resources (Cepeda-Cornejo and Dirzo 2010).…”
Section: Discussionsupporting
confidence: 90%
“…Sexual dimorphism is another important axis of genetic variation that underlies variation in ecologically important traits and may thus have consequences for plant-associated arthropod communities (Petry et al 2013). In particular, the separation of reproductive roles in dioecious plants (separate males and females) has been hypothesized to drive divergence in resource allocation between males and females (Lloyd and Webb 1977;Delph 1999).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Petry et al (2013) also found that insect predators were more abundant on female plants in a system based on Valeriana edulis. The present study is unique in that it shows not only predictable plant sex effects on the densities of herbivores and predators, but also on the predation pressure on the herbivores, as well as a mechanism involving plant effects on predator performance as a candidate key driver behind the observed patterns.…”
Section: Discussionmentioning
confidence: 82%